2019
DOI: 10.1590/0100-5405/178478
|View full text |Cite
|
Sign up to set email alerts
|

Compostos voláteis de fungos conidiais sapróbios da Amazônia Meridional no controle in vitro de fitopatógenos

Abstract: RESUMO Estudos sobre compostos orgânicos voláteis (COVs) produzidos por fungos conidiais sapróbios da Amazônia (FCSA) ainda são inexistentes. Assim, verificou-se a produção de COVs de FCSA e, seu potencial no controle de fitopatógenos in vitro. Utilizou-se os FCSA Beltrania rhombica, Brachysporiella sp., Dictyochaeta sp., Gonytrichum sp. e avaliou-se a produção de COVs através da germinação e viabilidade de esporos dos fitopatógenos e, crescimento micelial, conforme metodologias de (2) e (10), com adaptações. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These fungi have a characteristic rusticity, allowing them to adapt to the conditions of the environment, and there are no reports that they cause diseases in plants; however, they induce defense mechanisms such as phytoalexins (Solino et al 2017). Oliveira et al (2019) reported the production of volatile compounds by saprobic conidial fungi from the southern Amazon that reduce spore germination, mycelial growth rate, and production of survival structures and inhibit mycelial growth of phytopathogens, indicating their potential for biological control of diseases and promoting plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…These fungi have a characteristic rusticity, allowing them to adapt to the conditions of the environment, and there are no reports that they cause diseases in plants; however, they induce defense mechanisms such as phytoalexins (Solino et al 2017). Oliveira et al (2019) reported the production of volatile compounds by saprobic conidial fungi from the southern Amazon that reduce spore germination, mycelial growth rate, and production of survival structures and inhibit mycelial growth of phytopathogens, indicating their potential for biological control of diseases and promoting plant growth.…”
Section: Introductionmentioning
confidence: 99%